Hubungan antara Intensitas Mengakses Informasi Pariwisata Akun Instagram @indtravel dan Intensitas Komunikasi Word of Mouth dengan Minat Wisatawan Mancanegara Berkunjung ke Indonesia - Arum Fatimah, Zahra; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Tourism industry is among the fast growing industry in Indonesia. The previous studies and surveys found that social media and word-of-mouth are usually used by tourists to look for information and recommendations about tourim destination and other tourism related information. This study aims to analyse the relation between intensity of accessing tourism-related information on @indtravel and word-of-mouth communication to the intention of foreign tourists to visit Indonesia. This explanatory-quantitative research used the basic concept of Theory Reasoned Action, Computer Mediated Communication (CMC) Model, and Theory of Uses and Gratification along with the previous journals to explain the relation between each of the independent variabels to the dependen variabel, which is the intention of foreigner to visit Indonesia. The data of the research was collected through online questionnaire, with the targeted sample size of 75 respondents. The method for the sampling technique is purposive sampling since the respondents are chosen by the nationality and those who are actively following @indtravel on Instagram. The econometric computer software SPSS, is used to statistically analyzed the data collected through survey. The results of this study shows that there is a relation between the intensity of accessing tourism-related information on @indtravel and word-of-mouth communication to the intention of foreign tourists to visit Indonesia.